2011
DOI: 10.1111/j.1750-3841.2011.02380.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Determination of d‐Glucosamine Hydrochloride in Health Foods by HPLC Using 7‐Fluoro‐4‐Nitrobenzo‐2‐Oxa‐l,3‐Diazole as a Derivative

Abstract: This article presents an improved method to detect D-glucosamine hydrochloride in health foods. A simple precolumn derivatization procedure with 7-flouro-4-nitrobenzo-2-oxa-1,3-diazole (NBD-F) reagent was employed. The separation of the derivatized D-glucosamine hydrochloride (NBD-D-glucosamine hydrochloride) was performed using a mobile phase consisting of acetonitrile, potassium dihydrogen phosphate (0.01 mol/L), and trifluoroacetic acid (350:649.74:0.26, volume ratio) at a flow rate of 1.0 mL/min with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A common liquid chromatographic mode is RPHPLC on a C 8 or C 18 column with various detectors. Way et al have suggested a refractive detector (Way, Gibson, & Breite, 2000), but typically (after derivatization) either UV detection (Lopez-Cervantes, Sanchez-Machado, & Delgado-Rosas, 2007;Su, Wang, Chi, Li, & Shao, 2011;Kosman, Karlina, Pozharitskaya, Shikov, & Makarov, 2017) or more sensitive fluorescence detection has been applied Nemati, Valizadeh, Ansarin, & Ghaderi, 2007;Ibrahim & Jamali, 2010). Recently, also MS detection has been reported for a pharmacokinetic study (Song, Hang, Wang, Yang, & Wen, 2012).…”
mentioning
confidence: 99%
“…A common liquid chromatographic mode is RPHPLC on a C 8 or C 18 column with various detectors. Way et al have suggested a refractive detector (Way, Gibson, & Breite, 2000), but typically (after derivatization) either UV detection (Lopez-Cervantes, Sanchez-Machado, & Delgado-Rosas, 2007;Su, Wang, Chi, Li, & Shao, 2011;Kosman, Karlina, Pozharitskaya, Shikov, & Makarov, 2017) or more sensitive fluorescence detection has been applied Nemati, Valizadeh, Ansarin, & Ghaderi, 2007;Ibrahim & Jamali, 2010). Recently, also MS detection has been reported for a pharmacokinetic study (Song, Hang, Wang, Yang, & Wen, 2012).…”
mentioning
confidence: 99%